Transsynaptic Retrograde Degeneration: Clinical Evidence with Homonymous RGCL Loss on OCT - Meier, P.; Maeder, P.; Borruat, F.-X. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background: Retinal thinning after a retrogeniculate lesion (transsynaptic retrograde degeneration) was first described 50 years ago, but has long been a controversial issue. It is now possible to use OCT for the in vivo measurement of retinal thickness. Material and Methods: This was a retrospective study of patients with homonymous visual field loss, with SD-OCT assessment (RNFL and RGCL measurements) in isolated retrogeniculate lesions, subsequently confirmed by a neuroradiologist. Results: Nine patients with vascular, inflammatory or tumour brain lesions were included in the study. Homonymous RGCL thinning was found in all patients, and correlated with the visual field defect. No correlation was found with RNFL. Conclusions: The homonymous defect of RGCL in patients with retrogeniculate lesions demonstrates the presence of transsynaptic retrograde degeneration. RGCL is a better predictor of visual field defects than RNFL measurement.
Keywords: retrogeniculate lesion; homonymous retinal ganglion cell loss; homonymous hemianopia; spectral domain optical coherence tomography